Komunikasi Pemasaran Hutan Bambu Sebagai Destinasi Wisata Kota Bekasi - Sukoco, Iwan; Prihadini, Diana; Suryani, Octavia (LUGAS Jurnal Komunikasi, 2022)
A tourist destination is a certain geographical area or area within one or more  administrative areas that is distinct and has an element of tourist attraction. At  this  time  many  tourist  spots  do  promotions  with  marketing  communications.  Marketing communication is a means used by companies in an effort to inform,  persuade, and remind consumers both directly and indirectly about the products  and brands they sell. The purpose of this study was to analyze the marketing  communication strategies, marketing communication constraints, and marketing  communication solutions that occur at Hutan Bambu Tourism Sites. This study  used  a  qualitative  approach  with  a  descriptive  method.  The  data  were  collected  by interview, observation, and documentation. The results of this study indicated  that the marketing promotion activities carried out by the Hutan Bambu Manager  have not gone well, the indicator is because of the limited budget they have so  Marketing Promotion activities  cannot  be  carried out  optimally.